ANALISIS FATWA DSN-MUI No. 116/DSN-MUI/IX/2017 TENTANG UANG ELEKTRONIK SYARIAH TERHADAP PRAKTIK PENGGUNAAN APLIKASI DANA - Dafa Rizqi Maulana; Abu Bakar; Nanda Himmatul Ulya (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
This research is to find out the practice of using DANA electronic money and Analysis of DSN-MUI fatwa No.116/DSNMUI/IX/2017 concerning Sharia Electronic Money on DANA Electronic Money Practices. This research uses the type of emperis research. The data source uses primary data in the form of observation and documentation, while secondary data is in the form of books, journals, theses, and articles that discuss electronic money to reinforce data collection. The collection techniques of this research are observation and documentation. The data was analyzed using the descriptive analysis method. Then, the data was checked for validity using member-check. The results of this study indicate that the practice of using DANA electronic money has several stages; starting from downloading the DANA application, registering DANA by providing the terms and conditions of DANA registration to verify the electronic money account, and then topping up the balance (top up) on DANA, and the last stage of the DANA account can be used to transact and make payments on various features in it. Fatwa DSN-MUI No. 116/DSN-MUI/IX/2017 explains several rules that include general provisions, laws, contracts and related legal personnel, facility service fees, organization and use of electronic money, special provisions, and problem-solving. All of these provisions are following the use of DANA which has been explained previously. This fatwa was issued because the development of electronic money issued by banks and non-banks is growing, so it requires a sharia explanation of the limits and legal provisions related to electronic money. Based on the analysis of user practices and the fatwa, it can be concluded that DANA fulfils the provisions listed in the fatwa.